New Cucurbitane Triterpenoids and Steroidal Glycoside from Momordica charantia - Jie‐Qing Liu; Jianchao Chen; Cuifang Wang; Ming‐Hua Qiu (2009)
Three new cucurbitane triterpenoids 1–3 and one new steroidal glycoside 4, were isolated together with ten known compounds from Momordica charantia. The structures of new compounds were determined to be 19(R)-n-butanoxy-5β,19-epoxycucurbita-6,23-diene-3β,25-diol 3-O-β-glucopyranoside (1), 23-O-β-allopyranosylecucurbita-5,24-dien-7α,3β,22(R),23(S)-tetraol 3-O-β-allopyranoside. (2), 23(R),24(S),25-trihydroxycucurbit-5-ene 3-O-{[β-glucopyranosyl(1→6)]-O-β-glucopyranosyl}-25-O-β-glucopyranoside (3), and 24(R)-stigmastan-3β,5α,6β-triol-25-ene 3-O-β-glucopyranoside (4), respectively. Their structures were elucidated by the combination of mass spectrometry (MS), one and two-dimensional NMR experiments and chemical reactions.